PENGARUH KARAKTERISTIK KEPEMIMPINAN KHARISMATIK (MODEL CONGER-KANUNGO) TERHADAP TIPE KEPEMIMPINAN LAINNYA - Netania Emilisa (Media Riset Bisnis & Manajemen, 2007)
The general objective of this research is to determine the indicator characteristics in Conger —Kanungo model that can be use to scale charismatic leadership in internasional bank in Jakarta, and to analyze influence of charismatic leadership characteristics in Conger — Kanungo model to another leadership style. According to the research, the result all characteristics in Conger-Kanungo model can be use to scale charismatic leadership. There are influence from charismatic leadership (Conger-Kanungo Model) to all another leadership style. This is show relationship between characteristics charismatic with Task-Oriented Leadership, relationship between environmental sensitivity, vision and articulation with participative leadership, relationship between vision and articulation, sensitivity to member needs to people oriented leadership dan relationship between sensitivity to member needs, vision and articulation with Bass Charisma Scale.Keywords : Charismatic Leadership, Task-Oriented Leadership. Participative Leadership, People-Oriented Leadership, Bass Charisma Scale